ТРИФАЗНІ ВИМІРЮВАЛЬНІ КАНАЛИ ВЕКТОРІВ НАПРУГИ ТА СТРУМУ, ЇХНІЙ ВПЛИВ НА ТОЧНІСТЬ ВИМІРЮВАНЬ - Стогній, Б.С.; Сопель, М.Ф.; Варський, Г.М.; Яковлева, І.В. (Інститут електродинаміки НАН України, Київ, 2013)
The operation of three-phase metering circuits of vectors of voltage and current is considered. The concept of the threephase measuring channel has been defined and features of work of instrument transformers in its structure have been shown. The mathematical modeling is used to study and estimate the effect of asymmetry of input signals and loadings of instrument transformers on a measurement accuracy of vectors of voltage in such channels depending on resistance of the neutral lead of the communication line. Change of loadings of current transformers as a part of the three-phase measuring channel from asymmetry of input signals has been studied. On a concrete example influence of this factor on errors of transformers has been estimated. The necessity of use of mathematical models of three-phase measuring channels to define correcting amendments for increase of a measurement accuracy of vectors has been proved. Practical recommendations of construction of three-phase measuring channels are given. References 6, table 1, figures 5.